Short Communication: The existence of Homalomena rubescens (Araceae) in Java, Indonesia based on morphological and molecular evidence - ARIFIN SURYA DWIPA IRSYAM; MUHAMMAD RIFQI HARIRI; NADIA NAFARISA KAMILA; MUHAMMAD FABIO RAYHAN KURNIAWAN; ICHSAN SUWANDHI; RINA RATNASIH IRWANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Irsyam ASD, Hariri MR, Kamila NN, Kurniawan MFR, Suwandhi I, Irwanto RR. 2023. Short Communication: The existence of Homalomena rubescens(Araceae) in Java, Indonesia based on morphological and molecular evidence. Biodiversitas 24: 3821-3827. Homalomena Schottis a member of Araceae family, with most species originating from Southeast Asia. Due to its stunning heart-shaped leaves and tolerance to shade, H. rubescens (Roxb.) Kunthis frequently used as an ornamental plant and is frequently found in tropical gardens. As an ornamental plant, it can escape cultivation. The existence of H. rubescens in Java has been enigmatic, and the likelihood of misidentification is high because it has morphological characteristics in common with H. pendula (Blume) Bakh.f. This research aims to confirm the presence of H. rubescens in Java, Indonesia based on examination of morphological characters and molecular analysis. An adventive population of Homalomena rubescens was found in the Babakan Siliwangi City Forest, Bandung City, West Java, as a result of a field study in 2022. Materials of the population were then collected and made into specimens in the Herbarium Bandungense for further morphological observations. Additionally, a molecular approach was used to confirm the identity. The collected specimen is unquestionably H. rubescens (Roxb.) Kunth based on morphological and molecular analysis. Therefore, in this paper, we formally announced H. rubescensas a newly naturalized species in Java, Indonesia.